Topology and ferroelectricity in group-V monolayers*Project supported by the National Natural Science Foundation of China (Grant Nos. 11974307 and 61574123), Zhejiang Provincial Natural Science Foundation, China (Grant No. D19A040001), the Fundamental Research Funds for the Central Universities of China, and the 2DMOST, Shenzhen University (Grant No. 2018028). (May 2020) - Rehman, Mutee Ur; Hua 华, Chenqiang 陈强; Lu 陆, Yunhao 赟豪
Abstract : The group-V monolayers (MLs) have been studied intensively after the experimental fabrication of two-dimensional (2D) graphene and black phosphorus. The observation of novel quantum phenomena, such as quantum spin Hall effect and ferroelectricity in group-V elemental layers, has attracted tremendous attention because of the novel physics and promising applications for nanoelectronics in the 2D limit. In this review, we comprehensively review recent research progress in engineering of topology and ferroelectricity, and several effective methods to control the quantum phase transition are discussed. We then introduce the coupling between topological orders and ferroelectric orders. The research directions and outlooks are discussed at the end of the perspective. It is expected that the comprehensive overview of topology and ferroelectricity in 2D group-V materials can provide guidelines for researchers in the area and inspire further explorations of interplay between multiple quantum phenomena in low-dimensional systems.